KEBIJAKAN EKSPOR PASIR LAUT PASCA DIUNDANGKAN PERATURAN PEMERINTAH NOMOR 26 TAHUN 2023 BERDASARKAN PRESPEKTIF TEORI SISTEM HUKUM - Dwi Lestari Indah Sari (Jurnal Hukum Samudra Keadilan, 2023)
Provisions regarding the export of sea sand have long been banned and have now been legalized again with the promulgation of Government Regulation Number 26 of 2023 concerning Management of Sedimentation Products in the Sea which has raised various resistances from activists and environmental movements. an act will affect the legal system in society. According to Lawrence M Friedman, the legal system consists of three important components, namely substance which relates to the content of a legal product, legal structure which relates to the producer of legal products and legal culture which relates to the attitudes and expectations of society towards law. In this study, we will discuss how Government Regulation Number 26 of 2023 is from the perspective of the legal system according to Lawrence M Friedman.